2012
DOI: 10.1134/s1995423912020012
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical approach of seismic full waveform inversion

Abstract: Full waveform inversion (FWI) of seismic traces recorded at the free surface allows the reconstruction of the physical parameters structure on the underlying medium. For such a reconstruction, an optimization problem is defined, where synthetic traces, obtained through numerical techniques as finite-difference or finite-element methods in a given model of the subsurface, should match the observed traces. The number of data samples is routinely around 1 billion for 2D problems and 1 trillion for 3D problems whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Bozdag et al (2011), Wu et al (2014) and Chen et al (2018) introduced a reflection multiscale envelope inversion method so that the signal's envelope carries ultra-low frequency information missing in the original signal. Furthermore, a set of methods have been developed to exclude the cycle-skipped events in different domains (Bunks et al, 1995;Asnaashari et al, 2012;Bi and Lin, 2014;AlTheyab and Schuster, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bozdag et al (2011), Wu et al (2014) and Chen et al (2018) introduced a reflection multiscale envelope inversion method so that the signal's envelope carries ultra-low frequency information missing in the original signal. Furthermore, a set of methods have been developed to exclude the cycle-skipped events in different domains (Bunks et al, 1995;Asnaashari et al, 2012;Bi and Lin, 2014;AlTheyab and Schuster, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Multi-component data have been used in full waveform inversion in both the acoustic and elastic formulations in the time and frequency domain, including methods attempting to incorporate the advantages of both time and frequency domain formulations. Such inversion methods often incorporate nested hierarchical workflows (Choi et al, 2008;Brossier et al, 2009;Asnaashari et al, 2012;Plessix et al, 2013;Prieux et al, 2013;Yang et al, 2014, and others). The possibility of poro-elastic FWI has also been considered (Yang et al, 2018;Yang and Malcolm, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Cycle-skipped events are excluded by filtering in different transform domains (Bunks et al, 1995;Asnaashari et al, 2012), or by evaluating the phase lag between the observed and calculated data for each event and muting cycle-skipped events (Bi and Lin, 2014). In general, such methods apply FWI in multistages.…”
Section: Introductionmentioning
confidence: 99%